THE ROLE OF FOLDING AND FOLIATION DEVELOPMENT IN THE GENESIS OF MEDIAL MORAINES: EXAMPLES FROM SVALBARD GLACIERS - Hambrey M.J.; Glasser N.F. (My University, 2003)
The structure and debris content of four glaciers in NW Spitsbergen (Svalbard) are described to test the hypothesis that medial moraines are the product of folding, accompanied by the development of longitudinal foliation. Using clast orientation, clast shape, and clast lithological data, combined with measurements of fold axes and foliation in ice, this hypothesis is shown to be applicable to small valley glaciers with multiple basins feeding a narrow tongue, a common situation in Svalbard. The glaciers examined show stratification (commonly incorporating angular rockfall-derived debris) folded to varying degrees along flow-parallel axes throughout the tongue. An axial plane foliation is commonly associated with this folding and attains its greatest strength at flow-unit boundaries. The debris takes a medium-level to high-level transport path through the glacier, emerging at point sources defined by gently dipping fold hinges near the snout. As more of the folded debris layer melts out, downglacier-widening medial moraines are formed. In a few locations, foliation containing basally derived debris also shows an axial planar relationship with folding; this debris typically melts out to produce diamicton with predominantly subrounded and subangular clasts. In this case, it is inferred that subglacial sediment and debris-rich basal ice are folded within the body of the glacier and can reach the surface near the snout. The proglacial areas preserve evidence of medial moraines in the form of trains of coarse angular debris and foliation-parallel ridges of diamicton, although the latter have a poor preservation potential. There is scope for applying these structural glaciological concepts to medial moraines wherever glaciers are fed by multiple basins. [PUBLICATION ABSTRACT]
Keywords: GLACIERS; GEOLOGY